Modelling of a microreactor on heterogeneous surface and an influence of microreactor geometry - Baronas, R.; Ivanauskas, F.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 1998)
A model of an action of the amperometric biosensors based on carbon paste electrodes encrusted with single microreactor is analyzed. The model is based on non stationary diffusion equations containing non-linear term related to the enzymatic reaction. The biosensors current, which is a function of the concentration gradient of the reaction product on the electrodes, is used for analyzing of dynamics of the reaction. An influence of a size of microreactor, a geometrical form of microreactor and a position of microreactor on the biosensors action is investigated.
Keywords: biosensor; microreactor; diffusion-reaction; modelling